Perylene‐Fused, Aggregation‐Free Polycyclic Aromatic Hydrocarbons for Solution‐Processed Distributed Feedback Lasers. Issue 35 (25th June 2020) - Zou, Ya; Bonal, Víctor; Moles Quintero, Sergio; Boj, Pedro G.; Villalvilla, José M.; Quintana, José A.; Li, Guangwu; Wu, Shaofei; Jiang, Qing; Ni, Yong; Casado, Juan; Díaz‐García, María A.; et al.
Abstract: Perylene‐fused, aggregation‐free polycyclic aromatic hydrocarbons with partial zigzag periphery (ZY‐01, ZY‐02, and ZY‐03 ) were synthesized. X‐ray crystallographic analysis reveals that there is no intermolecular π–π stacking in any of the three molecules, and as a result, they show moderate‐to‐high photoluminescence quantum yield in both solution and in the solid state. They also display the characteristic absorption and emission spectra of perylene dyes. ZY‐01 and ZY‐02 with a nearly planar π‐conjugated skeleton exhibit amplified spontaneous emission (ASE) when dispersed in polystyrene thin films. Solution‐processed distributed feedback lasers have been fabricated using ZY‐01 and ZY‐02 as active gain materials, both showing narrow emission linewidth (<0.4 nm) at wavelengths around 515 and 570 nm, respectively. In contrast, ZY‐03 did not show ASE and lasing, presumably due to its highly twisted backbone, which facilitates nonradiative internal conversion and intersystem crossing. Abstract : Novel organic lasers were fashioned from large, aggregation‐free polycyclic aromatic hydrocarbons (PAHs). Several new perylene‐based PAHs were prepared that show perylene‐like electronic properties with moderate fluorescence quantum yields. Two of them show amplified spontaneous emission, and solution‐processed distributed feedback lasers were successfully fabricated.